2014
DOI: 10.1021/cs5009927
|View full text |Cite
|
Sign up to set email alerts
|

A Cobalt Hydride Catalyst for the Hydrogenation of CO2: Pathways for Catalysis and Deactivation

Abstract: The complex Co­(dmpe)2H catalyzes the hydrogenation of CO2 at 1 atm and 21 °C with significant improvement in turnover frequency relative to previously reported second- and third-row transition-metal complexes. New studies are presented to elucidate the catalytic mechanism as well as pathways for catalyst deactivation. The catalytic rate was optimized through the choice of the base to match the pK a of the [Co­(dmpe)2(H)2]+ intermediate. With a strong enough base, the catalytic rate has a zeroth-order dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 67 publications
3
102
0
1
Order By: Relevance
“… 13 For example, Fujita et al reported a Cp*Co (Cp* = η 5 -C 5 Me 5 ) complex supported by a dihydroxy-bipyridine ligand that is capable of 59 turnovers to formate in aqueous bicarbonate, 14 while Linehan and coworkers described an even more impressive TON of 9400 using (Me 2 PCH 2 CH 2 PMe 2 ) 2 CoH, although the use of a costly and strong base (Verkade's base) is required for high conversion. 15 During the same time period, Beller and coworkers described both cobalt and iron catalysts supported by tetraphosphine ligands, with the [P( o -C 6 H 4 PPh 2 ) 3 Fe] 2+ congener affording the highest TON for an iron catalyst to date. 16 This in situ generated system afforded 1897 turnovers to formate in methanol/water with excess NEt 3 under 60 atm of CO 2 /H 2 at 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“… 13 For example, Fujita et al reported a Cp*Co (Cp* = η 5 -C 5 Me 5 ) complex supported by a dihydroxy-bipyridine ligand that is capable of 59 turnovers to formate in aqueous bicarbonate, 14 while Linehan and coworkers described an even more impressive TON of 9400 using (Me 2 PCH 2 CH 2 PMe 2 ) 2 CoH, although the use of a costly and strong base (Verkade's base) is required for high conversion. 15 During the same time period, Beller and coworkers described both cobalt and iron catalysts supported by tetraphosphine ligands, with the [P( o -C 6 H 4 PPh 2 ) 3 Fe] 2+ congener affording the highest TON for an iron catalyst to date. 16 This in situ generated system afforded 1897 turnovers to formate in methanol/water with excess NEt 3 under 60 atm of CO 2 /H 2 at 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Mit diesem System konnte sogar unter Atmosphärendruck und Raumtemperatur eine TOF von 3400 h −1 und eine TON von 2000 erhalten werden. Unter Verwendung von DBU als Base wurde noch immer eine TOF von 220 h −1 bei Raumtemperatur und 40 bar Gesamtdruck erzielt . In Anwesenheit der schwächeren Base NEt 3 konnte keine Reaktion beobachtet werden.…”
Section: Ameisensäure/co‐stufeunclassified
“…The transformation of carbon dioxide into reduced, higher value molecules, such as methanol and formic acid, is of great interest for both environmental and economic reasons. In solution, ligand‐protected transition metal hydride complexes, L n MH, often play important roles in these processes . The critical reduction step involves the insertion of the C=O group of carbon dioxide into the M−H bond to produce a formate–metal adduct, L n M‐OC(O)H, from which the formate product can be generated.…”
Section: Figurementioning
confidence: 99%